2017
DOI: 10.1093/jscr/rjx044
|View full text |Cite
|
Sign up to set email alerts
|

Extensive small bowel intramural haematoma secondary to warfarin

Abstract: Intramural haematoma is a rare complication of oral anticoagulant therapy, occurring in  1 in 2500 patients treated with warfarin. This report describes a 71-year-old gentleman who presented with tachycardia, vomiting and abdominal distension on a background of anticoagulation for a metallic aortic valve. He was found to have a supratherapeutic international normalized ratio (INR) of 9.9 with an extensive small bowel intramural haematoma and secondary small bowel obstruction. He was successfully managed non-op… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 8 publications
0
10
2
Order By: Relevance
“…The incidence of bowel hematoma was reported to be 1/2500 per year in patients receiving warfarin, and the incidence is relatively higher in males (Bettler et al, 1983). Limmer and Clement (2017) reported a case of successful conservative treatment of bowel hematoma caused by overdose anticoagulation with warfarin in a 71-year-old man. Shaw et al (2005) reported one case of small-bowel hematoma in a child who received therapeutic doses of LMWH because of deep venous thrombosis.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of bowel hematoma was reported to be 1/2500 per year in patients receiving warfarin, and the incidence is relatively higher in males (Bettler et al, 1983). Limmer and Clement (2017) reported a case of successful conservative treatment of bowel hematoma caused by overdose anticoagulation with warfarin in a 71-year-old man. Shaw et al (2005) reported one case of small-bowel hematoma in a child who received therapeutic doses of LMWH because of deep venous thrombosis.…”
Section: Discussionmentioning
confidence: 99%
“…Predisposing factors for spontaneous intramural hematoma include bleeding diathesis, hematological malignancies, vasculitis, chemotherapy, H. Pylori infection, colonic diverticular bleeding, angiodysplasia, or iatrogenic injuries such as endoscopic biopsy. 2 Moreover, in patients with the history of cardiac surgery, myocardial infarction should also be ruled out. 3,8,10 At first instance, making a precise diagnosis of warfarininduced intramural hematoma before doing an invasive approach is difficult and it requires high clinical judgment to prevent unnecessary exploratory surgeries.…”
Section: Discussionmentioning
confidence: 99%
“…1 It also can present as a rare complication of anticoagulant therapy, especially warfarin. 2 The small intestine is the most common site affected by spontaneous intramural hematoma and intramural hematoma of the colon is really rare. Because of the rarity of spontaneous colon hematoma, often the diagnosis is not suspected.…”
Section: Introductionmentioning
confidence: 99%
“…Most studies consist of case reports or series. Studies have reported effective non-operative management with nasogastric decompression, bowel rest, and correction of coagulopathy [8,[12][13][14]. A review of the literature revealed two case studies wherein poisoning lead to coagulopathic small bowel hematomas resulting in obstruction.…”
Section: Discussionmentioning
confidence: 99%